Development of a plant microbiome bioremediation system for crude oil contamination. Issue 4 (August 2021) - Saeed, Maimona; Ilyas, Noshin; Arshad, Muhammad; Sheeraz, Muhammad; Ahmed, Iftikhar; Bhattacharya, Arghya
Abstract: Bacterial-assisted phytoremediation is recently being considered to be an efficient technique for remediation of crude oil-contaminated soil. The present research was designed to establish a plant microbiome bioremediation system for treating crude oil contamination. 10 strains of plant growth-promoting rhizobacteria (PGPR) were isolated from oil-contaminated soil near Oil Refinery Rawalpindi, Pakistan. Based on plant growth-promoting characteristics and biosurfactant production, two strains ( Pseudoarthrobacter phenanthrenivorans (MS2) and Azospirillum oryzae (MS6)) were selected. They showed a better emulsification index (54.2, 42.5%), oil displacement activity (3.4, 2.6 mm), and hydrophobicity content (78, 75%, ). For the establishment of the plant microbiome system, both strains and their combination were inoculated in rhizospheric soil of maize in crude oil-contaminated soil. Better germination attributes of maize were observed by a combination of both strains with improved fresh (32%) and dry biomass (26.5%) as compared to control under oil stress (10%). Plant microbiome bioremediation system improved the chlorophyll content (30.4%), water potential (23.2%), proline (32%), amino acids (11.1%), and antioxidant enzymes (catalase (21%), peroxidase dismutase (30%) and superoxide dismutase (22%), as compared to control under oil stress (10%). The hydrocarbons degradation efficiency of this system was 38.5%. Analysis of degradation products by GC-MS revealed the presence of low molecular weight hydrocarbons in the treated soil as compared to untreated soil. This study showed promising results by this plant microbiome system can be a way forward in bacterial assisted phytoremediation approaches at the field level in the future. Graphical Abstract: ga1 Highlights: Two strains ( Pseudoarthrobacter phenanthrenivorans and Azospirillum oryzae ) were isolated from oil-contaminated soil. Plant growth-promoting characteristics and hydrocarbons degradation of strains and their combination was checked. Establishment of plant microbiome system for remediation of crude oil contaminated soil. Hydrocarbon degradation of plant microbiome system was confirmed by GC-MS analysis. The plant-microbe system showed the degradation efficacy and also increased dry weight, chlorophyll content, and antioxidant enzymes in maize.